2014
DOI: 10.1002/14651858.cd006866.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment for preventing postherpetic neuralgia

Abstract: There is high quality evidence that oral aciclovir does not reduce the incidence of PHN significantly. In addition, there is insufficient evidence to determine the effect of other antiviral treatments; therefore, further well-designed RCTs are needed to investigate famciclovir or other new antiviral agents in preventing PHN. Future trials should pay more attention to the severity of pain and quality of life of participants, and should be conducted among different subgroups of people, such as people who are imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 41 publications
3
123
0
9
Order By: Relevance
“…Administration of varicella zoster immunoglobulin (VZIG) as postexposure prophylaxis is recommended for individuals with a significant exposure to varicella or zoster, who have a clinical condition that increases their risk of severe varicella and are seronegative for VZV [22]. Use of antiviral agents such as aciclovir, valaciclovir, and famciclovir to treat zoster reduces the severity and duration of illness [35,36] but may not be associated with a reduction in post-herpetic neuralgia [37]. Developing vaccines to reduce the population burden of VZV disease has therefore been an important goal.…”
Section: Epidemiology Of Varicella and Herpes Zostermentioning
confidence: 99%
“…Administration of varicella zoster immunoglobulin (VZIG) as postexposure prophylaxis is recommended for individuals with a significant exposure to varicella or zoster, who have a clinical condition that increases their risk of severe varicella and are seronegative for VZV [22]. Use of antiviral agents such as aciclovir, valaciclovir, and famciclovir to treat zoster reduces the severity and duration of illness [35,36] but may not be associated with a reduction in post-herpetic neuralgia [37]. Developing vaccines to reduce the population burden of VZV disease has therefore been an important goal.…”
Section: Epidemiology Of Varicella and Herpes Zostermentioning
confidence: 99%
“…Therapeutic approaches include symptomatic treatments, antibiotics to treat bacterial superinfections, antiviral therapy, and nerve blocks [41]. Disease guidelines highlight the importance of beginning antiviral therapy early, if possible within 72 h from symptom onset, in order to avoid loss of efficacy [42].…”
Section: Clinical Aspects and Epidemiologymentioning
confidence: 99%
“…Proof of a positive effect of antivirals on PHN would require a randomized controlled study of patients with PHN. Most studies, however, have not found antiviral therapy to be effective in the treatment of PHN 74 and regulatory authorities do not recommend antivirals to treat this condition 75 .…”
Section: Neurological Complications Of Zostermentioning
confidence: 99%
“…Antiviral therapy should be initiated within 3 days of the onset of rash if possible, but should still be initiated if patients are seen later with continuing new lesion formation. Although antiviral therapy reduces acute pain associated with zoster, it has not been shown to reliably reduce the risk of PHN, nor is it recommended to treat established PHN 74 . Prednisone reduces acute pain and improves the ability of patients with zoster to perform activities of daily living 184 ; however, prednisone does not reduce the risk of PHN 185 and many elderly patients have conditions such as hypertension, diabetes mellitus or osteoporosis, which may preclude the use of this drug.…”
Section: Zoster and Phnmentioning
confidence: 99%